THE EFFECT OF TURMERIC ACID ON PERINEAL WOUND HEALING IN POSTPARTUM WOMEN IN PMB KARANGPLOSO AREA, MALANG DISTRICT - salama, asaluka billah (Journal of Islamic Medicine, 2024)
Perineal rupture is a laseration or wound that develops along the perineum during the delivery process, which can occur accidentally or intentionally. (episiotomi). Perineum wounds resulting in childbirth can potentially cause infection because the germs enter through the seams. Kunyit works in several stages to speed up wound healing. Curcuma domestica Val contains curcumin compounds that can accelerate re-epithelisation, cell proliferation, and collagen synthesis. (Wientarsih et al, 2012). Java acid works as an antibacterial, anti-inflammatory, analgesic and antioxidant activity. The aim is to analyze the effect of acid turmeric on the healing of perineal wounds in postpartum mothers. The method used in this study is the type of pre-experiment with design intact-group comparison. The study used variables with two groups, including the experimental group and the control group. The sample totaled 32 mothers with a perineal injury. The results of the study were that the average wound healing control group got 3-5 REEDA scores of 8 people with presentations (50%) and the experimental group got 0-2 REEDE scors of 14 people with presentation (87,5%). The Mann-Whitney Statistical Test was conducted by Asymp. Sig. (2-tailed) / p.value is worth 0,000. Because the value is 0,000 of 0.05, it means there is an effect of acid curcumin on the healing of perineal wounds.